Immortalization and Characterization of Bone Marrow Stromal Fibroblasts from a Patient with a Loss of Function Mutation in the Estrogen Receptor‐α Gene - Dieudonné, S. C.; Xu, T.; Chou, J. Y.; Kuznetsov, S. A.; Satomura, K.; Mankani, M.; Fedarko, N. S.; Smith, E. P.; Robey, P. Gehron; Young, M. F. (Journal of bone and mineral research, 1998)
A male patient with abnormal postpubertal bone elongation was shown earlier to have a mutation in both alleles of the estrogen receptor, resulting in a nonfunctional gene. Marrow stromal fibroblasts (MSFs) derived from this patient were called HERKOs (human estrogen receptor knock outs), and in order to obtain continuous HERKO cell lines, they were immortalized using a recombinant adenovirus‐origin‐minus SV40 virus. MSFs are unique cells because they support hematopoesis and contain a mixed population of precursor cells for bone, cartilage, and fat. Three established cell lines (HERKO2, HERKO4, and HERKO7) were characterized and compared with the heterogeneous population of nonimmortalized HERKOs for their osteogenic potential. We performed Northern analysis of matrix genes implicated in bone development and metabolism and an in vivo bone formation assay by transplanting the cells subcutaneously into immunodeficient mice. All three HERKO lines expressed high amounts of collagen 1A1, osteopontin, osteonectin, fibronectin, decorin, biglycan, and alkaline phosphatase. Except for osteopontin, expression of these genes was slightly lower compared with nonimmortalized HERKOs. In the in vivo bone formation assay, the heterogeneous population of nonimmortalized HERKOs formed bone with high efficiency, while the HERKO lines induced a high‐density, bone‐like matrix. Finally, all HERKO cell types secreted high levels of insulin‐like growth factor I and interleukin‐6 into the culture medium relative to cells of normal human subjects. In summary, these lines of HERKO cells retain several of the phenotypic traits of MSFs after immortalization, including matrix and cytokine production, and provide a valuable source of a unique human material for future studies involving estrogen action in bone and bone marrow metabolism.